Pelaksanaan Perjanjian Peminjaman Uang Antara Bumdes Dengan Masyarakat Desa Pandan Indah : (Studi di Desa Pandan Indah, Kecamatan Praya Barat Daya, Kabupaten Lombok Tengah) - Ahmad Jayadi; Shinta Andriyani; Mohammad Irfan (Fakultas Hukum Universitas Mataram, 2023)
This study's purpose is to determine the implementation of loan agreements between BUMDes and the community and to find out the causes of bad loans at BUMDes Pandan Indah, Praya Barat Daya District, Central Lombok Regency. This research is a normative-empirical legal research and uses the statute approach, the conceptual approach, and the sociological approach. The results of this study that the implementation of the loan agreement is divided into 2 stages, namely the first stage, submit an application by the customers and completing the requirements set by BUMDes Pandan Indah, and the second stage is the signing of the loan agreement which before the applicant or customer receives the money. The causes of bad loans at BUMDes Pandan Indah consist of internal causes and external causes.